(untitled) (Islamic Sciences Journal, 2023)
Morphological weighting explanation is the interpretation for the weighting of linguists and morphologists. After the linguist or morphologists come up with evidence to reinforce one of the two issues، given that a cause is what the object exists and is outside the object in flouncing it. The rationale to explain the judgments received: one of the four pillars of measurement ، each measure has four things: origin ،branch ،cause and judgment. This topic has been investigated in a number of pure reasons as: the reason of lightness and heaviness the bug of the same ،and the bug pay illusion.